Análise de sentimentos em Rede Social: Pandemia do Coronavírus no Brasil - Rosa, William Matheus (2021)
Social networks are places with a lot of users. There, people from around the world share their feelings about most diverse subjects, which means the texts published on social media can be explored to try to understand what a certain public thinks about a specific subject. Sentiment Analysis arises from the need to understand what is the feeling in these texts in a productive way, due to the great amount of connected users. Through the data that is extracted from the texts, useful information for decision-making is generated. This article presents the sentiment analysis of Twitter, during the Coronavirus pandemic in Brazil, it was possible to perceive better reactions after the vaccination period started.